Lo start up delle reti tra imprese. Analisi dei gap tra “intenzione” e “(inter-)azione” - Grippo, Giovanna; Marchiori, Michela; Tunisini, Annalisa (Piccola Impresa / Small Business, 2016)
Management literature has studied the difficulties and conditions underlying the creation of business networks. The study of the processes involved in the phase between the creation and the implementation of business networks is still limited. The aim of the paper is to contribute knowledge to fill the gap of research on this issue, assuming the so-called “network contracts”. In Italy the number of network contracts formally constituted has increased over the years. However, the take-off of these networks is limited Therefore, this paper aims to analyse the main variables involved in the different stages of development of the network contracts and highlights the factors that can promote or limit their start-up. To this end, we will refer to the literature on inter-organizational relationships and on business networks, and to the results of an empirical research conducted on two network contracts in the food industry showing different outcomes.